Seven secrets of COVID-19: fever, ACE2 receptors, gut-lung axis, metabolomics, microbiomics, probiotics, diet - Vassilios Fanos; Roberta Pintus; Maria Cristina Pintus; Michele Mussap; Maria Antonietta Marcialis (Hygeia Press di Corridori Marinella, 2021)
The aim of this work is to investigate 7 secrets of COVID-19 (fever, ACE2 receptors, gut-lung axis, metabolomics, microbiomics, probiotics, diet), hoping to reveal a small part of some of these and to increase anyhow the knowledge on SARS-CoV-2 and its weaknesses to be able to defeat it. In particular, in the opinion of the authors, significant improvements in contrasting the Coronavirus, and the pandemics that will follow, could derive from the use of "omics" disciplines, namely metabolomics (the stethoscope of the future) and microbiomics (an unrecognized player). The discovery of new biomarkers using metabolomics could be used in clinical practice as predictive diagnostic tools or to evaluate the effectiveness and toxicity of a drug, in order to be able to provide the patient with a personalized, tailor-made medicine: precision medicine. Our understanding of the role of the gut microbiome in COVID-19 infection remains in its infancy, but future research may potentially aid our understanding of viral infection, and create new ways in which we might treat and prevent it. We strongly believe that the 3 M's (Metabolomics, Microbiomics and Machine learning [Artificial Intelligence]) will be the right route to the future for risk assessment, early diagnosis, patient management and decision-making. By now, probiotics could help, fighting face to face against the virus. Moreover, the diet may be a key driver in determining the severity of COVID-19 and further studies are needed to explore the secret language between diet, bacteria, viruses and metabolites in determining individualized susceptibility or resilience to COVID-19.